Akt Promotes Survival of Cardiomyocytes In Vitro and Protects Against Ischemia-Reperfusion Injury in Mouse Heart - Yasushi Fujio; Thao Nguyen; Detlef Wencker; Richard N. Kitsis; Kenneth Walsh (2000)
Background —IGF-1 has been shown to protect myocardium against death in animal models of infarct and ischemia-reperfusion injury. In the present study, we investigated the role of the IGF-1–regulated protein kinase Akt in cardiac myocyte survival in vitro and in vivo. Methods and Results —IGF-1 promoted survival of cultured cardiomyocytes under conditions of serum deprivation in a dose-dependent manner but had no effect on cardiac fibroblast survival. The cytoprotective effect of IGF-1 on cardiomyocytes was abrogated by the phosphatidylinositol 3-kinase (PI 3-kinase) inhibitor wortmannin. Wortmannin had no effect on cardiomyocyte viability in the absence of IGF-1. IGF-1–mediated cytoprotection correlated with the wortmannin-sensitive induction of Akt protein kinase activity. To examine the functional consequences of Akt activation in cardiomyocyte survival, replication-defective adenoviral constructs expressing wild-type, dominant-negative, and constitutively active Akt genes were constructed. Transduction of dominant-negative Akt blocked IGF-1–induced survival but had no effect on cardiomyocyte survival in the absence of IGF-1. In contrast, transduction of wild-type Akt enhanced cardiomyocyte survival at subsaturating levels of IGF-1, whereas constitutively active Akt protected cardiomyocytes from apoptosis in the absence of IGF-1. After transduction into the mouse heart in vivo, constitutively active Akt protected against myocyte apoptosis in response to ischemia-reperfusion injury. Conclusions —These data are the first documentation that Akt functions to promote cellular survival in vivo, and they indicate that the activation of this pathway may be useful in promoting myocyte survival in the diseased heart.